MICROFINANCE AND SME LENDING: CHALLENGES AND OPPORTUNITIES IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
This study examines the current state, challenges, and opportunities of microfinance and small and medium enterprise (SME) lending in Uzbekistan's rapidly evolving financial sector. Using a mixed-methods approach incorporating statistical analysis, literature review, and policy document examination, we analyze data from 2022-2025 covering 218 microfinance institutions and the broader SME financing landscape. Results demonstrate explosive growth: microfinance loan volumes doubled to 21.3 trillion soums in the first nine months of 2025, while total microfinance services reached 66.9 trillion soums (up 1.9-fold). However, critical challenges persist: only 10% of small and 16% of medium enterprises access credit, creating a $6 billion financing gap. Key barriers include insufficient collateral, limited financial literacy, high interest rates (averaging 35.9%), and gender disparities (women-led businesses receive only 14% of SME loans despite owning 33% of enterprises). Opportunities emerge through digital transformation (69% of MFO loans now online), regulatory reforms including collateral-free lending up to 100 million soums, and international support programs targeting 7,000 MSMEs by 2030. This research contributes empirical evidence on Uzbekistan's microfinance evolution and provides actionable recommendations for policymakers, financial institutions, and development organizations to enhance financial inclusion and SME sector growth.